Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

to prove

Asked by 20th February 2009, 5:17 PM
Answered by Expert
Answer:

(p x q). [(q x r) x (r x p)]

= (p x q). [ r ( (qxr).p ) - p ( (qxr).r ) ]

here (qxr) . r = 0  then

=(p x q). [ r ( (qxr).p ) ]

= (pxq).r [ q r p]    ( [q r p ] =  [p q r ] )

= [p q r ] [p q r ]

= [p q r ]2

Answered by Expert 20th February 2009, 11:22 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp